A Study to Assess the Prevalence of Self-medication and Its Associated Factors Among Pregnant Women in Selected Tertiary Care Teaching Hospital at Kuppam, Chittoor District, Andhra Pradesh - B. Aswini Priya; M.N. Pavithra; J. Balalakshmi; V. Divya Sri (International Journal of Midwifery Nursing And Practices, 2024)
Self-medication, the practice of using medications without a doctor's prescription, is a growing global public health issue, particularly in resource-limited settings. In pregnancy, self-medication can pose serious risks, including misdiagnosis, incorrect dosages, drug interactions, and prolonged use. This study aimed to assess the prevalence of self-medication, and the factors associated with it among pregnant women at a tertiary care teaching hospital in Kuppam, Chittoor district, Andhra Pradesh. A descriptive cross-sectional survey design was used with a non-probability purposive sampling technique to select 200 pregnant women. Data were collected through structured interviews and organized into four sections: socio-demographic variables, maternal variables, a checklist on self-medication prevalence, and factors associated with self-medication. Descriptive and inferential statistics were used for data analysis. The study found that 49% of pregnant women reported using self-medication. Among them, 87.8% consumed medication rarely, 67.3% for headaches, and 78.5% used topical medications. The primary factors contributing to self-medication included lack of time to visit a hospital (70.4%), minor health issues (72.4%), convenience (77.5%), and financial constraints (37.7%). Significant associations were found between self-medication and factors such as educational qualification (p
Keywords: Healthcare; Pregnant women; Prevalence; Self-medication; associated factors